Role in regulating the economy, the budget system of the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
"The central place is the state budget in the financial system – it is the largest pool of money that the government uses to finance its operations. Due to its special situation the state budget interacts with other parts of the financial system, providing them with necessary support."
Keywords: The budget; budget Policy